Pendampingan Penguatan Keagamaan Anak Melalui Metode Makharijul Huruf dan Yanbu’a di Pondok Pesantren Hidayatul Mustaqim Bulusari Tarokan Kediri - Rudianto; Abd Majid Abror (LP3M IAIFA Kediri, 2020)
Religious assistance in question is an activity that contains Islamic religious learning such as The Qur'an, makharijul letters and yanbu'a. This community assistance activity is seen as quite successful in resuscitating the community about the current environmental conditions. In mentoring also emerged good cooperation and communication between researchers and parties concerned and the role of the community of Bulusari Village actively in succeeding the program. The number of children who follow the activities and abilities displayed by children during the race also shows the success of learning in order to strengthen religion for children. All participants were awarded prizes either winning or losing showed a thorough appreciation for children to continue to carry out religious activities that have the full support of the family and society. The success of this program can also be used as a model of implementing religious reinforcement elsewhere by adjusting the existing context.